Confronting the evidence a call to reopen the 9/11 investigation - Walter, Jimmy; Charles, Leany; ReOpen911.org ([Santa Barbara, CA.] : ReOpen911.org)
Investigate all the evidence and the curiosity on September 11 attach includes how could such a large plane leave a hole so small and answered what is that attached to the small bottom of the plan
Title from title screen
Chices of languages: English, Italiano, Francais, Deutsh, Netherlands, Espanol, Chinese and Arabic
Host: Ed. Begley, Jr.
Co-Host: Jeamy Hecht
Keywords: September 11 Terrorist Attacks, 2001; Terrorism -- United States